ANALISIS KEBIJAKAN PENDIDIKAN INDONESIA (UU NO 20 TAHUN 2003) - Sahriah; Auliyaputri, Nurul; Saleh, Sirajuddin; Mualim, Dita Adelia; Faisal; Najib, Muh; Nabila, Nur (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Education in Indonesia, as one of the pillars of national development, faces significant challenges in achieving equitable quality and relevance to global needs. Law Number 20 of 2003 concerning the National Education System (UU Sisdiknas) serves as the primary legal basis for the implementation of education in Indonesia. This article examines the education policies contained in the Law Sisdiknas, focusing on their goals, objectives, effectiveness, efficiency, and impact on the national education system. Although these policies have successfully increased access to education, disparities in quality across regions and social groups remain a major issue. Evaluations indicate that the policies' effectiveness in improving education quality has been suboptimal, particularly in achieving the goals of developing student character and competency. Efficiency challenges also arise related to unequal budget distribution and differing managerial capacities across regions. This article also proposes alternative policies that can strengthen the Indonesian education system, such as transforming education financing to focus more on quality, changing the evaluation system to be more holistic, and improving educator competency. It is hoped that this study will provide useful insights for improving and adapting education policies to current demands. Keywords: Education Policy, Law Sisdiknas, Education Effectiveness, Education Efficiency, Policy Alternatives, National Education